Taurodontism, variations in tooth number, and misshapened crowns in Wnt10a null mice and human kindreds. Issue 1 (15th September 2014) - Yang, Jie; Wang, Shih‐Kai; Choi, Murim; Reid, Bryan M.; Hu, Yuanyuan; Lee, Yuan‐Ling; Herzog, Curtis R.; Kim‐Berman, Hera; Lee, Moses; Benke, Paul J.; Kent Lloyd, K. C.; Simmer, James P.; et al.
Abstract WNT10A is a signaling molecule involved in tooth development, and WNT10A defects are associated with tooth agenesis. We characterized Wnt10a null mice generated by the knockout mouse project (KOMP) and six families with WNT10A mutations, including a novel p.Arg104Cys defect, in the absence of EDA, EDAR, or EDARADD variations. Wnt10a null mice exhibited supernumerary mandibular fourth molars, and smaller molars with abnormal cusp patterning and root taurodontism. Wnt10a−/− incisors showed distinctive apical–lingual wedge‐shaped defects. These findings spurred us to closely examine the dental phenotypes of our WNT10A families. WNT10A heterozygotes exhibited molar root taurodontism and mild tooth agenesis (with incomplete penetrance) in their permanent dentitions. Individuals with two defective WNT10A alleles showed severe tooth agenesis and had fewer cusps on their molars. The misshapened molar crowns and roots were consistent with the Wnt10a null phenotype and were not previously associated with WNT10A defects. The missing teeth contrasted with the presence of supplemental teeth in the Wnt10a null mice and demonstrated mammalian species differences in the roles of Wnt signaling in early tooth development. We conclude that molar crown and root dysmorphologies are caused by WNT10A defects and that the severity of the tooth agenesis correlates with the number of defective WNT10A alleles.